The African Union's Economic, Social and Cultural Council : an evaluation of its mandate of facilitating civil society participation in the African Union - Habib, Mohamed (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.